Sublevel open stoping : design of the O640, L651 and N659 sub-level open stopes in the 3000 orebody of the Mount ISA copper mines, Queensland, Australia - Sloane, Lomar (2013)
This dissertation will explore the process followed in the design of a sub-level open stope (SLOS) by using examples of actual stopes scheduled to be in production between August 2006 and February 2007. The main objective is to give the reader an understanding into sub-level open stoping and the design process followed. The objective here is to present a design methodology applicable to sublevel open stoping, but also to then bridge the gap between theory and practice by applying said methodology to an actual design example. The design examples used in this dissertation is based on the O640, L651 and N659 stopes in the 3000 Orebody of Xstrata Copper Operation’s Mount Isa Mine, located in North-West Queensland, Australia. The actual design reports as required by the mine are attached in Annexure 1 through 3. Given the similarities of the designs, only O640 will be analysed comprehensively within the main content of this report, with L651 and N659 discussed specifically insofar issues that were unique to these stopes. With the design of O640, all aspects or design considerations as stipulated in the design process were discussed and analysed so as to define the final stope shape. These design considerations include: Faulting Grade Contours Existing Development Surrounding Fill masses Rock Mechanics Once the the final stope shape has been set, options regarding stope extraction will take place. This is where the initial stope layout takes place and where the engineer looks at the advantages and disadvantages of all the different options available in mining the stope. In this phase, the most effective extraction option is decided upon. Once the engineer have decided a final stope shape and extraction option, the stope will be analysed in further detail referring to drilling, the amount of drawpoints, ventilation and other stoping requirements. These are all defined as stope design features and are considered a general summary of the stope design. The design features phase is closely followed with all the safety considerations that have been taken into account since the stope design started. Main concerns and stope specific safety issues are discussed and possible solutions given. It is part of the work of the mine planning engineer to anticipate all possible safety issues and make the production department aware of what can be expected during the development, mining and filling activities of every stope. At this stage the design of the stope nears completion. The remainder of the design now goes into more detail and addresses the critical tasks that from part of sub-level open stoping. These include: Reserves and Scheduling Development and Drilling Production and Firing (Blasting) Ventilation Services Filling Economic Analysis Although all of the abovementioned have already been mentioned during the design features phase, it is still required to give additional details so the different departments involved have an accurate idea of what to expect, when to expect it and therefore be able to sufficiently plan for it. It must be noted that it does happen that something may be “discovered” during any stage of the final design, which may render the current design undesirable. When this happens the stope must be re-designed until all issues have been resolved or at the least have been managed appropriately. Even though this report does not go into detail with the L651 and N659 designs, these designs are included as they bring to light issues that may arise that are unique to individual stopes. L651 looks at how a design drastically changes when ore not planned for is discovered. N659 looks at what happens when a stope is the first to be mined in an area with inadequate infrastructure. The main content of the dissertation discusses and explains the design procedure as it would take place at Mount Isa Mines, but it is still quite difficult to follow logically. For this reason a flowchart was included to give the reader a more comprehensive summary of the design process. === Dissertation (MEng)--University of Pretoria, 2011. === Mining Engineering === unrestricted